APPLICATION OF DEVELOPED SOLID FOAMING AGENTS TO REMOVE LIQUID FROM THE BOTTOM OF GAS AND GAS CONDENSATE WELLS - Oripova , Shakhlo; Akramov, Bakhshillo; Adizov, Bobirzhon (Innovatsion texnologiyalar, 2024)
Problems with fluid accumulation at the bottom arise during the operation of gas and gas condensate wells. Since the number of fields that have passed the final stage of development is constantly growing, the problem of removing well fluid is becoming increasingly urgent. The reason for the accumulation of liquid at the bottom of the well is the gas flow rate insufficient for complete removal. There are various ways to solve this problem, one of the most important of which is the use of solid and liquid surfactants. The use of solid surfactants is the most economical and accessible method for removing fluid from the bottom of wells. Anionic surfactants were used in the studies. Based on the research results, solid surfactant compositions were developed that foam a mixture of condensation and formation water. Solid surfactant samples form powerful foam; the developed solid surfactants samples remove a large amount of liquid from the bottomhole zone of the well. The created solid surfactants, is economical and import-substituting since most of the reagents used in the composition of the created solid surfactants, consist of waste local raw materials.